Pengaruh Praktek Good Coorporate Governance terhadap Nilai Perusahaan Perbankan di Indonesia - Yossi Eko Sriyanto Putra; Elisabeth Penti Kurniawati (Universitas Kristen Maranatha, 2017)
Abstract Bank Indonesia has ever imposed sanctions against several banks in Indonesia for not implementing good corporate governance. This case will certainly affect the public perception of the value of banking companies in Indonesia. The objective of this research is to analyze the effect of Good Corporate Governance on Company Value on the banking sector listed on the Indonesia Stock Exchange in a period of 2012-2014. The components of good corporate governance used in this study are the Institutional Ownership, Managerial Ownership, Audit Committee, and Independent Commissioner. The Company Value is measured by Tobin’s Q. The sampling method in this research is a purposive sampling method. This study uses secondary data in the form of annual reports obtained from the website of the Indonesia Stock Exchange. Hypothesis testing in this study uses multiple linear regression analysis technique. The results show that good corporate governance does not affect the company value in the banking sector companies. Nevertheless, this study may indicate that good corporate governance is essential for the company, though not enough to affect the value of a company. Keywords: Good Corporate Governance (GCG); Company Value